Pengaruh Substitusi Bungkil Inti Sawit Terhadap Karakteristik Proksimat dan Organoleptik Tempe dengan Penambahan Ragi 0,2% - Simanjuntak, Rivana Debora; Giyanto, Giyanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the effect of palm kernel cake (PKC) substitution on the proximate and organoleptic characteristics of tempe using 0.2% yeast. The increasing dependence on imported soybeans encourages the utilization of alternative raw materials such as PKC, which is abundantly available as a by-product of the palm oil industry. This study used a completely randomized design with three treatment levels, namely PKC substitution of 20%, 40%, and 60%. Proximate analysis was carried out descriptively, while organoleptic data were analyzed using ANOVA and continued with Duncan’s test based on the assessment of 10 panelists. The results showed that increasing PKC concentration increased ash and crude fiber content, while protein and fat content decreased, and moisture content remained relatively stable. Organoleptic evaluation indicated that the 20% substitution level had the highest acceptance. Statistical analysis showed significant effects on color, taste, and overall acceptance, but not on aroma and texture. These findings indicate that PKC has potential as a substitute material in tempe production, although higher concentrations reduce consumer acceptance. Practically, this study suggests that palm kernel cake can be utilized at an optimal substitution level (20%) in the food industry to produce nutritionally valuable, cost-effective, and acceptable tempe products.